2019
DOI: 10.1029/2019gl084822
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Electron Flux Enhancement and Butterfly Pitch Angle Distributions on L Shells <2.5

Abstract: We analyze an energetic electron flux enhancement event in the inner radiation belt observed by Van Allen Probes during an intense geomagnetic storm. The energetic electron flux at L~1.5 increased by a factor of 3 with pronounced butterfly pitch angle distributions (PADs). Using a three‐dimensional radiation belt model, we simulate the electron evolution under the impact of radial diffusion, local wave‐particle interactions including hiss, very low frequency transmitters, and magnetosonic waves, as well as Cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 56 publications
(83 reference statements)
0
18
0
Order By: Relevance
“…Van Allen Probes measurements are used to update the electron PSDs at the lower energy boundary, and we set the electron PSDs at the upper energy boundary to be constants. We take f=0 $f=0$ inside the bounce loss cone, and Dααfα+Dαpfp=0 ${D}_{\alpha \alpha }\frac{\partial f}{\partial \alpha }+{D}_{\alpha p}\frac{\partial f}{\partial p}=0$ at αeq=90° ${\alpha }_{\text{eq}}=90{}^{\circ}$ following previous studies (Albert et al., 2016; Hua et al., 2019).…”
Section: Upper Limit Of Electron Acceleration By Chorus Waves From Si...mentioning
confidence: 99%
“…Van Allen Probes measurements are used to update the electron PSDs at the lower energy boundary, and we set the electron PSDs at the upper energy boundary to be constants. We take f=0 $f=0$ inside the bounce loss cone, and Dααfα+Dαpfp=0 ${D}_{\alpha \alpha }\frac{\partial f}{\partial \alpha }+{D}_{\alpha p}\frac{\partial f}{\partial p}=0$ at αeq=90° ${\alpha }_{\text{eq}}=90{}^{\circ}$ following previous studies (Albert et al., 2016; Hua et al., 2019).…”
Section: Upper Limit Of Electron Acceleration By Chorus Waves From Si...mentioning
confidence: 99%
“…In addition, at energies above several hundred keV, the pitch angle scattering by LGW and hiss causes electron scattering loss on a shorter timescale than the electron acceleration by transmitter waves (Agapitov et al., 2014; Claudepierre et al., 2020a; Green et al., 2020; Meredith et al., 2007). The electron acceleration by transmitter waves may be also slower than the transport process of radial diffusion and injections (e.g., Hua et al., 2019; Ma, Li, et al., 2017). Therefore, the electron acceleration effect by transmitter waves may be weak under most circumstances.…”
Section: Diffusion Coefficients Of Transmitter Wavesmentioning
confidence: 99%
“…Recent studies suggest that MS waves can scatter radiation belt electrons by both Landau and bounce resonances (S. Fu et al, 2019; and scatter ring current protons by cyclotron resonance (Fu et al, 2016;Fu & Ge, 2021). Hua et al (2019) shed light on the possible cause of consecutively attendant butterfly PADs at 1.5 ≤ L ≤ 1.8, that is, attributed to inward propagation of butterfly PADs formed at higher radial regions due to MS waves. By performing a statistical analysis of energetic electron PAD characteristics based on Van Allen Probes (VAPs) observations, C. Yang, Su et al (2017) found that energetic electron butterfly distributions in the slot region are primarily caused by MS waves.…”
mentioning
confidence: 93%
“…Hua et al. (2019) shed light on the possible cause of consecutively attendant butterfly PADs at 1.5 ≤ L ≤ 1.8, that is, attributed to inward propagation of butterfly PADs formed at higher radial regions due to MS waves. By performing a statistical analysis of energetic electron PAD characteristics based on Van Allen Probes (VAPs) observations, C. Yang, Su et al.…”
Section: Introductionmentioning
confidence: 99%